2020
DOI: 10.1002/slct.202002684
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Biological Evaluation of New Thieno[2,3‐g]indolizine Derivatives

Abstract: An effective approach to the synthesis of thieno[2,3‐g]indolizine derivatives has been developed. A wide variety of reagents such as unsaturated aldehydes, methylvinylketone, esters of acrylic acid, maleic anhydride, methyl propiolate, dimethyl and diethyl acetylenedicarboxylates in the construction of functionally diverse rarely encountered tricyclic system has been used. A high number of structurally various thieno[2,3‐g]indolizines has been obtained in domino reactions with medium and high yields, the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[72] Voskressensky's group showed that the interaction of aroyl formic acids 227 with 2-(thiophen-2-yl)ethylamine 226, and further refluxing of the product with POCl 3 led to the formation of compounds 228 in 65-83 % yield (Scheme 70). [73] The resulting 4-aroyl-6,7-dihydrothieno[3,2-c]pyridines 228 were studied in the domino-reactions with alkenes and alkynes containing electron-deficient groups.…”
Section: Obtaining Derivatives Of Thieno[g]indolizinesmentioning
confidence: 99%
“…[72] Voskressensky's group showed that the interaction of aroyl formic acids 227 with 2-(thiophen-2-yl)ethylamine 226, and further refluxing of the product with POCl 3 led to the formation of compounds 228 in 65-83 % yield (Scheme 70). [73] The resulting 4-aroyl-6,7-dihydrothieno[3,2-c]pyridines 228 were studied in the domino-reactions with alkenes and alkynes containing electron-deficient groups.…”
Section: Obtaining Derivatives Of Thieno[g]indolizinesmentioning
confidence: 99%
“…Boruah's group synthesized indolizines by using pyridine, bromoacetophenone, and alkyne under microwave conditions [21]. The aforementioned synthesis methods have established a solid foundation for the development and application of indolizine derivatives [22][23][24][25]. However, research on indolizine is still in its early stages.…”
Section: Introductionmentioning
confidence: 99%